1998
DOI: 10.1210/en.139.7.3081
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interferons-  and -  in Testicular Interstitial Tissue and Spermatogonia of the Rat

Abstract: The testis is divided into two compartments: the seminiferous tubules and the interstitial tissue. The latter essentially consists of the blood and lymphatic vessels, testosterone-producing Leydig cells, and testicular macrophages. In the exploration of the testicular antiviral defense system, we initially searched for interferon (IFN) production by the seminiferous tubule cells. The site of virus entry into the testis is probably the interstitial compartment; thus, it is important to know whether and how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…The testicular innate antiviral responses have been previously demonstrated based on a series of pioneering studies on the expression and regulation of both interferons (IFNs) and antiviral proteins in the testis by Professor Jégou's group. [60][61][62]95,96 These investigators also showed that several defensins are expressed in murine and human testes, and may contribute to the innate antimicrobial defense. 97 Recent studies have revealed that various PRRs are abundantly expressed in testicular cells and initiate testicular innate immune responses.…”
Section: Testicular Innate Immunitymentioning
confidence: 94%
See 1 more Smart Citation
“…The testicular innate antiviral responses have been previously demonstrated based on a series of pioneering studies on the expression and regulation of both interferons (IFNs) and antiviral proteins in the testis by Professor Jégou's group. [60][61][62]95,96 These investigators also showed that several defensins are expressed in murine and human testes, and may contribute to the innate antimicrobial defense. 97 Recent studies have revealed that various PRRs are abundantly expressed in testicular cells and initiate testicular innate immune responses.…”
Section: Testicular Innate Immunitymentioning
confidence: 94%
“…59 Previous studies demonstrated that rat Leydig cells exhibit innate antiviral ability in response to viral infection. 60,61 Human Leydig cells show relatively weak antiviral activity compared with rat cells. 62 These observations raise an interesting question whether the human testis has a weaker innate defense system against viral infection compared with the murine testis.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…The basal tubular position of these germ line precursors, a priori, exposes them to the risk of contamination in cases of viral infection. Despite the high potential risk of infection of spermatogonia, these cells do not constitutively express biologically active IFNs, and they respond only weakly to stimulation by Sendai virus in vitro (89). Similarly, early spermatids and pachytene spermatocytes, although expressing low levels of IFNs under basal conditions, respond very weakly if at all to exposure to Sendai virus (88).…”
Section: Testicular Antiviral Defense Systemmentioning
confidence: 99%
“…IFN-␣ and IFN-␥ are expressed in the testes (Dejucq et al, 1995(Dejucq et al, , 1998 and the hyperexpression of IFN-␣ and IFN-␤ in transgenic murine testes leads to infertility (Hekman et al, 1988;Iwakura et al, 1988). In contrast, administration of IFN-␣ enhances spermatogenesis in some infertile men increasing sperm number in the semen (Yamamoto and Miyake, 1994).…”
Section: Discussionmentioning
confidence: 99%